Study of Risk Management for Successful Project Accomplishment - Agarwal, Kushik; Goel, Anuj (Journal of Commerce and Trade, 2019)
Companies sometimes win a Project, not because of low price quoting, but because it had demonstrated to the owners, that the Company is having the best Risk Management Systems. Risk Management is an essential and important concept to be considered in all Project Management activities, especially in the contemporary Social and Economic Environment. Whenever we face a Risk, one of the biggest challenges is in deciding what to do about it. The word ’Risk’ itself sounds negative and implies a ’Threat to The Outcome’. This was the perception in earlier days, but this has changed nowadays. Earlier there was a lack of Structured Approach to study the Risk in project execution. Risk was addressed as and when deemed required. It was a ’situation based’ or a ’case by case’ reaction. Sometimes Contingencies Provisions were kept while preparing the estimate for covering an uncertain event; Mostly, some percentage was added to the Cost for Contingency. The situation changed once the organization started understanding the importance of Risk Analysis in Project Management. It was seen that the increases in contingencies expenditure narrowed the profit margin and delayed the project executions. On the other hand, too many provisions under the contingencies, decreased the competencies of a business. To strike a balance, the need was felt to analysis the Risk and address the impact under Project Management Principles. More Research is required to identify and quantify the Project Risks and to create Effective Risk Management Tools and Techniques. Classification-JEL : D81, G32, H43